2010
DOI: 10.2353/ajpath.2010.081063
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Protein and Nucleolin Colocalize in Breast Carcinoma Tissue and Cancer Cell Lines

Abstract: The breast and ovarian cancer susceptibility gene BRCA1 encodes a tumor suppressor. BRCA1 protein, which is involved in DNA damage response , has been thought to be found primarily in cell nuclei. In the present investigation , immunohistological studies of BRCA1 protein in frozen breast cancer tissue and MCF7 and HeLa cell lines revealed BRCA1 expression in both nucleoli and nucleoplasmic foci. The majority of known cancer-causing BRCA1 mutations induce protein truncation, highlighting a requirement for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…For the c-MYC pathway (Table 5) the higher ratios of EGFR transcript were associated with increased proteomic levels of branched chain amino-acid transaminase 1 (BCAT1), cytosolic, carbamoyl-phosphate synthetase 2 (CAD) and nucleolin (NCL), while higher ERBB2 ratios are associated with transferrin receptor (TFRC) and metadherin (MTDH). Examples of the significance of these proteins include the observation that nucleolin colocalizes with BRCA1 in breast carcinoma tissue 47 , and metahedrin is a valuable marker of breast cancer progression and high expression may play a role in tumorigenesis of breast cancer 4849 . As was observed for the EGFR pathway, most of the proteins in Table 4 (GRB2) and Table 5 (MYC) contained a significant number of interactors (12/17 and 28/31) and literature associations with cancer (16/17 and 24/31) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For the c-MYC pathway (Table 5) the higher ratios of EGFR transcript were associated with increased proteomic levels of branched chain amino-acid transaminase 1 (BCAT1), cytosolic, carbamoyl-phosphate synthetase 2 (CAD) and nucleolin (NCL), while higher ERBB2 ratios are associated with transferrin receptor (TFRC) and metadherin (MTDH). Examples of the significance of these proteins include the observation that nucleolin colocalizes with BRCA1 in breast carcinoma tissue 47 , and metahedrin is a valuable marker of breast cancer progression and high expression may play a role in tumorigenesis of breast cancer 4849 . As was observed for the EGFR pathway, most of the proteins in Table 4 (GRB2) and Table 5 (MYC) contained a significant number of interactors (12/17 and 28/31) and literature associations with cancer (16/17 and 24/31) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence-Cells were grown at low density on sterilized coverslips for 24 h. Cell sections were washed with PBS buffer three times and fixed in 4% paraformaldehyde for 15 min and processed for the immunofluorescence procedure as described previously (15). Primary antibodies used were rabbit anti-S100A14 (1:50) (gift from Dr. Iver Petersen) and mouse anti-HER2 (1:100) (sc-08, Santa Cruz Biotechnology, Inc., Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that BRCA1 protein is localized in tumor cell nuclei and nucleoli in frozen tissue sections, and is co-localized with nucleolin in MCF7 and HeLa cells [26,27]. Chambon et al [28] have shown in light and electron microscopic studies of estradiol-treated MCF7 cells that BRCA1 nuclear staining was found in dots around nucleoli, and in the cytoplasm in multivesicular bodies near the Golgi.…”
Section: Introductionmentioning
confidence: 99%